Estudo dos Homiinae (Hymenoptera, Braconidae) em remanescentes de Mata Atlântica Ombrófila do Brasil - Shimbori, Eduardo Mitio (2005)
In this work the efficiency of three traditional methods of collection of insects were analyzed and tested (Malaise trap, Moericke trap and "sweepings" of the vegetation) for studies of the subfamília Hormiinae and, separately, for the six more abundant sorts in the collections (Allobracon Gahan, 1915; Aspilodemon Fischer, 1968; Hormius, Nees, 1818; Pambolus Haliday, 1836; Pseudorhysipolis Scatolini & Penteado-Dias, 2002, and Rhysipolis Förster, 1862). The relation of this efficiency ea biology of the sorts briefly is argued. The technique of "sweepings" of the vegetation was the method most efficient for specimen collection of the majority of the sorts. The theories regarding the distribution of the species in a latitudinal gradient are argued on the basis of specimen samples of a subfamily of parasitoid insects, that seem to constitute an exception to the classic standard of distribution of the largest part of the organisms. The importance to consider the biology of the organisms and regional variables is pointed out. The gotten results corroborate with the consulted works and the hypotheses of geometric limits, energy of the environment and spalling of resources. Twelve new species and new occurrences for three sorts and two species for Brazil are cited. The distribution of the species in the points of collection and the South America is told and illustrated. The potential of new species is briefly commented with approach in the main sorts and also in the Northeast Region. Twelve new species of Allobracon Gahan, 1915 (Hymenoptera: Braconidae) are described and illustrated. All species described were collected in Brazilian Atlantic Forest. A key to species is added.